Olahraga Tradisional Menyipet Dan Balogo Di Masyarakat Kota Palangka Raya - Azahari, Abd Rahaman (FKIP, Universitas Palangka Raya, 2016)
Implications of the study as follows: reviewed from the aspects of social action, so the results of this study reinforce the theory of action Parsons, that